A high yielding rice variety, CRAM 3 (ARCC3Fa3L10P1-1-B-1) was released in Cote d'Ivoire for rainfed upland systems - CGIAR Research Program on Rice (2021)
CRAM 3 (ARCC3Fa3L10P1-1-B-1), a high yielding upland rice variety was released in Cote d'Ivoire in 2021.